Defining the predictors for post renal transplant left ventricular dysfunction in end‐stage renal disease patients - Mahboobeh Sheikhani; Hoorak Poorzand; Mahnaz Ahmadi; Negar Morovatdar; Sara Afshar; Zahra Shahinfar (Physiological Reports)
Abstract Reduced left ventricular (LV) function predicts poor outcomes in end‐stage renal disease (ESRD). This study aimed to identify the pre‐renal transplantation echocardiographic parameters that can predict post‐renal transplantation LV failure. This prospective longitudinal study was conducted on patients with ESRD who underwent renal transplantation during 1 year. All patients underwent echocardiography, including ejection fraction (EF), global longitudinal strain (GLS), left ventricular end‐systolic diameter (LVESD), left ventricular end‐diastolic volume (LVEDV), left ventricular end‐diastolic diameter (LVEDD), interventricular septal (IVS) thickness, peak velocity of early diastolic transmitral flow (E), peak velocity of late transmitral flow (A), early diastolic myocardial relaxation (Em), E/A, E/Em, Left atrial volume (LAV) index, tricuspid regurgitation peak gradient (TRPG), systolic pulmonary artery pressure (SPAP), tricuspid annular plane systolic excursion (TAPSE), 1 week before and 1 month after renal transplantation. Fifty patients participated in the current study. All echocardiographic parameters improved after transplantation. Post‐renal transplantation LV dysfunction was observed in 21 (42%) patients. Pre‐renal transplantation echocardiographic parameters (LVEDV, LVESD, LVEDD, IVS, E/Em, TRPG, SPAP, and LAV index) could predict post‐transplantation LV failure with high accuracy (AUC: 0.978).